1999
DOI: 10.1111/j.1151-2916.1999.tb01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Diamond‐Film Formation on Cobalt‐Cemented Tungsten Carbide

Abstract: The surface composition of cemented tungsten carbide (WC-5.8 wt% Co) was studied by X-ray photoelectron spectroscopy (XPS), during the early stages of diamondfilm deposition, by hot-filament chemical vapor deposition (HFCVD). The nucleated diamond films were analyzed by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and automatic image analysis (AIA). The evolution of the surface composition of cemented tungsten carbide during the early stages of diamond-film deposition was strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Consequently, the nucleation and growth of highquality diamond films, with reduced interfacial sp 2 -carbon formation, is possible onto WC-Co materials. However, under certain CVD conditions, the binder can diffuse through the ''etched layer'' up to the substrate surface and form Cocontaining clusters, as demonstrated by combined use of SEM and X-Ray Photoelectron Spectroscopy (XPS) [28]. Therefore, process conditions that favour either binder mobility or Co clustering during the diamond nucleation stage must be carefully avoided.…”
Section: Cobalt Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the nucleation and growth of highquality diamond films, with reduced interfacial sp 2 -carbon formation, is possible onto WC-Co materials. However, under certain CVD conditions, the binder can diffuse through the ''etched layer'' up to the substrate surface and form Cocontaining clusters, as demonstrated by combined use of SEM and X-Ray Photoelectron Spectroscopy (XPS) [28]. Therefore, process conditions that favour either binder mobility or Co clustering during the diamond nucleation stage must be carefully avoided.…”
Section: Cobalt Etchingmentioning
confidence: 99%
“…Samples were ultrasonically seeded for 15 min in 1/4 Am diamond suspension (Struers, DP-Suspension, HQ), then cleaned with ethanol in an ultrasonic bath. Diamond films were deposited for 9 h in a stainless steel hot-filament chemical vapor deposition (HFCVD) chamber described elsewhere [28]. The gas phase was composed of a mixture of methane and hydrogen with a CH 4 /H 2 volume ratio fixed at 1.0% and was activated using a tantalum filament (2170 -C).…”
Section: Use Of Interlayer Materialsmentioning
confidence: 99%
“…Nonetheless, the built-up of diamond films on WC-Co substrates is quite tricky because of the harmful effects of Co binder, which leads to the formation of a graphitic carbon layer at the substrate surface during the early stages of deposition, on which diamond grows later [3]. Mostly, the problem is overtaken by covering the WCCo substrate with interlayers, which act as diffusion barrier [4], etching the WC-Co substrate surface to wash superficial Co out [5], and decarburizing the substrate surface after the etching of binder [6].…”
Section: Introductionmentioning
confidence: 99%
“…Polini et al [26] showed that the nucleation of diamond on WC-Co substrates, which were pretreated in a way that was similar to the pretreatments used in this investigation, was independent of substrate grain size. However, in their study they used a conventional hot-filament CVD system to deposit the diamond films.…”
Section: Figures 4 and 5 Indicate That Co Out-diffusion Is Faster In Thementioning
confidence: 73%
“…This observation has been frequently reported by other workers. [25][26][27] Despite the Co fraction volume, with both types of substrates being the same the coarse-grain substrate showed greater density of such drops. Because the temperature of the coatings is below the liquid phase formation during cemented carbide sintering, it is expected that the drop formation (Fig.…”
Section: Cobalt Diffusionmentioning
confidence: 98%